Clinical and functional characteristics of Parkinson’s disease in patients with chronic kidney disease - F.A. Yusupov; M.Sh. Abdykadyrov; A.F. Yusupov (S.S. Korsakov Journal of Neurology and Psychiatry, 2026)
Objective. To evaluate the clinical and functional characteristics of Parkinson’s disease in patients with and without concomitant chronic kidney disease (CKD) and to assess the impact of renal dysfunction on motor, cognitive, and non-motor symptoms. Material and methods. A cross-sectional study was conducted involving 62 patients diagnosed with idiopathic Parkinson’s disease at stages I—III. The test group comprised 31 patients with an estimated glomerular filtration rate (eGFR) of 30—59 mL/min/1.73 m², while the control group comprised 31 patients with an eGFR of 60 mL/min/1.73 m² or higher. Various assessments were performed, including the Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS), Hoehn and Yahr Scale, Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and evaluations for depression, anxiety, and orthostatic dysfunction. Results. Demographic factors such as age, sex, and duration of Parkinson’s disease were similar between the groups; however, patients with CKD had a higher Hoehn and Yahr score (2.5 vs. 2.0; p